Government expenditure on households and vice versa. A SAM approach to Portugal - Santos, Susana (2009)
Through the use of aggregate Social Accounting Matrices for Portugal, the flows of funds from three government subsectors to households will be studied, as well as the flows from the latter to the former. From the SAM modelling, both a static and a comparative static analysis will be made, in order to specify the effects of changes in the flows of funds between households and government subsectors.